1992
DOI: 10.1002/1097-0142(19921215)70:12<2747::aid-cncr2820701204>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Production onf matrix metalloproteinase-2 and metalloproteinase-3 related to malignant behavior of esophageal carcinoma. A clinicopathologic study

Abstract: Background. Matrix metalloproteinases (MMP) are a gene family of zinc enzymes capable of degrading almost all of the extracellular matrix macromolecules in vivo. Their enzymic activities are believed to be responsible for tumor invasion and metastasis. Methods. In this study, using peroxidase‐antiperoxidase method, monospecific antisera against MMP‐1 (tissue collagenase), MMP‐2 (type IV collagenase/72‐kilo‐dalton [KD] gelatinase), and MMP‐3 (stromelysin) were applied to 29 squamous cell carcinomas and normal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
68
2
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 29 publications
9
68
2
2
Order By: Relevance
“…Intriguingly, both MMPs were more highly expressed in the metastatic regions than in the primary regions of OSCC, and this pattern was quite prominent in gingival cancers. The increased expression of MMPs correlates with the proliferation and invasion of tumor cells (16)(17)(18)(19)(20)(21)(22)(23). The enhancement of MMP activity in cultured cells indicates increased metastatic potential (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, both MMPs were more highly expressed in the metastatic regions than in the primary regions of OSCC, and this pattern was quite prominent in gingival cancers. The increased expression of MMPs correlates with the proliferation and invasion of tumor cells (16)(17)(18)(19)(20)(21)(22)(23). The enhancement of MMP activity in cultured cells indicates increased metastatic potential (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…The progression and invasion capacity of tumor is associated to with the degradations of basement membrane (which is formed by Type IV collagen), and the fibrous capsule (which is formed by Type I and Type III collagen). Due to the proteolytic activity of MMP-9 enzyme that degrades type IV collagen, it increases tumor invasion and progression (Shima et al, 1992;Kusukawa et al, 1993;Sato et al, 1999) Hong et al (2000) found the significant relationship between MMP-9 expression and cervical metastatic disease. The increased expression of MMP-9 in patients with oral squamous cell carcinoma was stated as 73.7% in contrast with our study, and any correlation with decrease in histological differentiation has not been established.…”
Section: Figure 3 A) the Staining Of Normal Epithelial Tissue For E-mentioning
confidence: 99%
“…Shima et al (1992) classified the stains of MMPs in oesophageal cancer into three groups. We, however, classified MMP-9 staining into two groups to simplify the data: negative, when the intensity of stain in cancer cells was negative or weaker than normal oesophageal epithelia; positive, when the intensity of staining was equal to or stronger than normal epithelia.…”
Section: Evaluation Of Immunohistochemical Stainingmentioning
confidence: 99%
“…We previously reported that the expression of vascular endothelial growth factor (VEGF) is associated with lymph node metastasis and prognosis in oesophageal cancer (Uchida et al, 1998). Other reports showed that the expression of matrix metalloproteinases (MMPs) (Shima et al, 1992), E-cadherin (Kadowaki et al, 1994;Nakanishi et al, 1997) and p53 (Wang et al, 1994) in primary tumours correlated with lymph node metastasis of oesophageal cancer.…”
mentioning
confidence: 99%